2007
DOI: 10.1213/01.ane.0000253485.75797.e7
|View full text |Cite
|
Sign up to set email alerts
|

Severe and Long-Lasting Complications of the Nerve Root and Spinal Cord After Central Neuraxial Blockade

Abstract: These findings suggest the influence of underlying spinal conditions in these complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 25 publications
0
34
0
5
Order By: Relevance
“…15 Atallah et al 16 used clinical parameters, such as age, BMI, spinal deformity, and quality of surface landmarks, as well as the radiological appearance of the lumbar spine (presence of osteophytes, ligamentous calcification, and narrowing of intervertebral spaces) to derive an 8-point difficulty score; a score of 4 or more was associated with higher difficulty. They further reported that the quality of surface landmarks and the radiological appearance of the spine were independent predictors of difficulty.…”
Section: Discussionmentioning
confidence: 99%
“…15 Atallah et al 16 used clinical parameters, such as age, BMI, spinal deformity, and quality of surface landmarks, as well as the radiological appearance of the lumbar spine (presence of osteophytes, ligamentous calcification, and narrowing of intervertebral spaces) to derive an 8-point difficulty score; a score of 4 or more was associated with higher difficulty. They further reported that the quality of surface landmarks and the radiological appearance of the spine were independent predictors of difficulty.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4]6,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Case reports of spinal haematoma after epidural analgesia are rare. 28 In fact, there is no report in conjunction with anticoagulation in the obstetric population.…”
Section: Discussionmentioning
confidence: 99%
“…За 10 років у Швеції пряме травмуван-ня голкою було виявлено лише в 9 із 1,7 мільйона випадків проведення нейроаксіальної анестезії (0,0005 %), і лише 1 випадок зафіксовано з 2000 до-сліджених випадків у французьких реабілітаційних центрах спинного мозку (з оціненого 1 мільйона нейроаксіальних анестезій, що проводилися того ж року в даному регіоні) [3,4].…”
Section: ятрогенна травма спинного мозкуunclassified